The Influence of AI Technology on Students' Academic Abilities and Cheating Behavior - Dakwan Soaloon Harahap (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine the effect of AI technology on students' academic abilities and cheating behavior. The research method used is systematic reviews from literature sources searched using the Google Scholar search engine. Several questions as research questions in this study are: 1) what is the effect of using AI technology on students' academic abilities?; 2) how is student cheating behavior linked to the use of AI technology? From the results of the literature review, it is known that the use of AI technology can improve students' academic abilities by making it easier to access information. However, there is an increase in the potential for cheating by students with AI technology in the form of students tending to avoid writing assignments because they rely on AI to do their writing assignments. It is recommended that policy makers in the education sector be able to regulate regulations on the use of AI for students to ensure that AI technology is utilized as well as possible without any misuse that leads to cheating or cheating.